Long-term changes in air quality. The case of Pristina (Kosovo) - Shala, Shkumbin; Aleksander-Kwaterczak, Urszula; Rexhepi, Fatos (Geology, Geophysics and Environment, 2022)
Rapid socio-economic development and urbanization have contributed to the serious deterioration of air quality in many world cities including Pristina, the capital of Kosovo. Through a data-driven analysis of regulatory intervention, this study attempts to examine the effectiveness of air pollution control regulations that have been implemented in Kosovo between 2010–2021. Our results show that the measures enforced during this 10-year period in Kosovo, and particularly in the capital city, have resulted in the reduction of pollution. The applied methods for this research are the standard ones of the Instituti Hidrometeorologjik i Kosovës (Hydrometeorological Institute of Kosovo). All results showed a decrease of each pollutant over the ten years. These changes strongly indicated that the origin of the pollution was traffic and anthropogenic activity, while the power plant was considered to be a less significant source of pollution. The basic pollutants of air quality in Pristina are particulate matter (PM2.5 and PM10), ozone and nitrogen oxide.